1989
DOI: 10.1073/pnas.86.12.4731
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a high-virulence clone of type III Streptococcus agalactiae (group B Streptococcus) causing invasive neonatal disease.

Abstract: Of the 44 isolates of type III from invasive episodes, 24 were cultured from blood, 18 were recovered from cerebrospinal fluid (CSF), and 1 each was grown from joint fluid and pulmonary secretions collected by tracheal aspiration. The 19 isolates from asymptomatic neonates were collected from the umbilicus (16 isolates), rectum (2 isolates), and throat (1 isolate). The sample also included isolates of types I (n = 8), lb (n = 16), Ic (n = 14), Ic/Il (n = 6), and II (n = 11) collected during disease episodes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
206
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(225 citation statements)
references
References 38 publications
(16 reference statements)
14
206
0
Order By: Relevance
“…One third of HA in a human body is overturned every day (37). The pathogenic strains of S. agalactiae that cause meningitis and septicemia and other serious diseases in humans, especially neonates, usually secrete more hyaluronate lyase to degrade HA and CS, two major kinds of polysaccharide components of the extracellular matrix (5). Mammals use endogenous hyaluronidases, a group of hydrolases, to accomplish the task of HA degradation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One third of HA in a human body is overturned every day (37). The pathogenic strains of S. agalactiae that cause meningitis and septicemia and other serious diseases in humans, especially neonates, usually secrete more hyaluronate lyase to degrade HA and CS, two major kinds of polysaccharide components of the extracellular matrix (5). Mammals use endogenous hyaluronidases, a group of hydrolases, to accomplish the task of HA degradation.…”
Section: Resultsmentioning
confidence: 99%
“…High levels of hyaluronate lyase (SagHL) were found in the extracellular cultures of the disease-causing strains of serotype III GBS (4 -6). Clinical studies indicated that strains of type III GBS that produce more extracellular hyaluronate lyase (division I S. agalactiae) are apparently more virulent than those strains producing less (division II S. agalactiae) (5,6). Division I S. agalactiae usually causes invasive infections, whereas division II bacteria cause diseases much less frequently and are usually found in asymptotically colonized infants.…”
mentioning
confidence: 99%
“…Nevertheless, high HylB levels or the presence of an intact hylB gene were also reported in isolates of S. agalactiae causing invasive disease. These contradictory reports point out that the exact involvement of HylB in systemic infections needs further investigations (Bohnsack et al, 2001;Musser et al, 1989;Rojo et al, 2008). IS1548 possesses another preferential insertion target just upstream of the lmb gene encoding a bifunctional laminin-binding protein/zinc-binding protein (Granlund et al, 1998(Granlund et al, , 2001; Fig.…”
Section: Mobile Genetic Element Of the Isas1 Familymentioning
confidence: 99%
“…A single homogeneous clone of capsular serotype III GBS (sequence type [ST] 17 ) was found to be significantly associated with cases of invasive neonatal disease (22). In the 1980s, Musser and colleagues (27) had also concluded that a single virulent clone was responsible for many cases of neonatal disease. Their work, based on multilocus enzyme electrophoresis, showed that a proportion of invasive neonatal GBS strains were genetically related and possessed capsular serotype III.…”
mentioning
confidence: 99%